Effectiveness of Good Corporate Governance and Corporate Social Responsibility Mechanisms on the Company's Financial Performance on the Indonesian Public Listed Companies: Pengaruh Mekanisme Good Corporate Governance dan Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan - Santi Yopie; Veronica Oktavia (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2023)
Business stocks with solid fundamentals, impressive performance, and liquid portfolios make up the KOMPAS100 index. This study is useful in determining the impact of corporate governance (GCG) and corporate social responsibility (CSR) systems on financial performance by using profit management as a mediation variable. This research is useful to determine the effect of corporate governance (GCG) and corporate social responsibility (CSR) mechanisms on financial performance. This considers the importance of theory in the inclusion of activities to be carried out by the company such as agency theory and legitimacy, agency is a theory that will bring together the company owner with the company manager, on the side the company manager can trigger problems due to differences in thinking with the owner of the company which will make profit management arise and then legitimacy where this theory is centered In one important core, namely sustainability, stakeholders will strive so that the company can continue to implement social interests by providing a positive response to the environment in which it operates. The purposive sampling strategy is used to select annual financial statements and reports from businesses included in the Kompas100 index for 2018 to 2021. The sample consisted of 32 businesses in total. Data processing and tabulation will be carried out using Eviews software version 12. The result of the analysis is that GCG and CSR have no influence on earning management. While earnings management has a significant positive effect on asset returns and Tobin's Q, but there is no effect on EPS. For GCG, it has a significant positive effect on asset returns but does not affect EPS and Tobin's Q. CSR has a significant negative effect on asset returns and Tobin's Q, but no effect on EPS.